CHANGES IN THE ORGANIZATIONAL STRUCTURE OF LOGISTICS ENTERPRISES IN THE CONDITIONS OF THE MODERN CRISIS - Stošić Mihajlović, Ljiljana; Jevtić Radulović, Marijana; Trajković, Svetlana (Journal of process management and new technologies, 2020)
In modern business conditions burdened by the crisis caused by the COVID-19 virus, all areas of life and work of modern civilization are deeply affected. All companies in modern economies have had a negative impact on the crisis. The logistics services sector is particularly affected. Companies that provide logistics services are now faced with a special requirement in terms of responding quickly to the challenges posed by quality logistics operations during a pandemic. For these reasons, as in other industries, companies in the logistics sector must adapt quickly to the challenges. The best way to adapt is to change the organizational structure of logistics companies, in accordance with the challenges imposed by the circumstances in the environment. This paper will discuss the necessary changes in the organizational structure of logistics companies, in order for these companies to continue or improve their business system, in accordance with the changes and challenges that come from the external environment.
Keywords: organizational structure; logistics; transport logistics; change management; crisis management,; , markets; COVID-19